Economic impacts of selected wellness SPAs in Tagaytay City - Palad, Victor Jacob Carandang; Salinoy, Denise Nicole; Jamandron, Cyrill John Malacca; Tabuyo, Jimford (Journal of Indonesian Tourism, Hospitality and Recreation, 2025)
AbstractTagaytay City, renowned for its cool climate and scenic landscape, has emerged as a popular destination for various types of tourism, including adventure, health, and wellness. This study evaluates the perceived economic impacts of wellness SPAs from the perspective of their customers. This study utilized a quantitative descriptive research design, with purposive sampling used to select respondents based on specific criteria. Data were gathered through an online survey distributed via social media platforms. Data were analyzed using frequency and percentage distributions, measures of central tendency such as mean and standard deviation, and inferential statistical methods including t-tests and ANOVA. The majority of respondents were female, aged 18–25, college graduates, and reported a monthly income exceeding ₱60,000. Findings revealed that wellness SPAs are widely perceived as significant contributors to the local economy, particularly through employment and income generation. Respondents also noted positive spillover effects on related sectors such as hospitality and tourism. Although induced impacts, such as enhancements in overall quality of life, were rated slightly lower, they were still viewed favorably. Perceptions were significantly influenced by age, educational attainment, and income level, while gender did not appear to have a notable effect. SPA operators and policymakers can use these insights to promote the local economic benefits of wellness tourism, while SPA managers can strengthen ties with local partners to boost customer loyalty and support sustainable growth.AbstrakKota Tagaytay, yang terkenal dengan iklim sejuk dan pemandangan alamnya yang indah, telah menjadi destinasi populer untuk berbagai jenis pariwisata, termasuk wisata petualangan, kesehatan, dan kebugaran. Penelitian ini menilai dampak ekonomi yang dirasakan dari keberadaan SPA dari perspektif para pelanggannya. Penelitian ini menggunakan desain penelitian deskriptif kuantitatif, dengan teknik purposive sampling untuk memilih responden berdasarkan kriteria tertentu. Data dikumpulkan melalui survei daring yang disebarkan melalui media sosial. Data dianalisis menggunakan distribusi frekuensi dan persentase, ukuran tendensi sentral seperti rata-rata dan simpangan baku, serta metode statistik inferensial termasuk uji t dan ANOVA. Mayoritas responden adalah perempuan berusia 18–25 tahun, lulusan perguruan tinggi, dan memiliki pendapatan bulanan lebih dari 17.000.000. Hasil penelitian menunjukkan bahwa SPA secara luas dipandang sebagai kontributor penting bagi perekonomian lokal, terutama melalui penciptaan lapangan kerja dan peningkatan pendapatan. Responden juga mencatat adanya efek limpahan positif terhadap sektor terkait seperti perhotelan dan pariwisata. Meskipun dampak tidak langsung, seperti peningkatan kualitas hidup secara keseluruhan, dinilai sedikit lebih rendah, namun tetap dipandang secara positif. Persepsi responden dipengaruhi secara signifikan oleh usia, tingkat pendidikan, dan tingkat pendapatan, sementara jenis kelamin tidak menunjukkan pengaruh yang berarti. Pemilik SPA dan pembuat kebijakan dapat menggunakan temuan ini untuk mempromosikan manfaat ekonomi lokal dari pariwisata kebugaran, sementara manajer SPA dapat memperkuat hubungan dengan mitra lokal untuk meningkatkan loyalitas pelanggan dan mendukung pertumbuhan yang berkelanjutan.